Comparisons of performances for determining the relative importance in the modern pentathlon - Seung-hun Lee; Jong-chul Park; Ki-bum Kim; Sung-jin Kim; Byoung-goo Ko (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to compare the official world records of UIPM in the last 3 years to find out the relationship between the score characteristics of fencing, swimming, equestrian, and laser-run events in the final rankings and to analyze the relative importance of each event. Methods For 3 years, from 2017 to 2019, a total of the data were collected, the final rankings, fencing conversion scores, swimming conversion scores, equestrian scores, and laser-run conversion scores for all male and female athletes who participated in the UIPM Level 1 World Cup and World Championships(1,197 finals and 2,173 qualifiers). The Multiple regression analysis was used to establish the relationship between the response(subjective) variable and the conversion score of the four explanatory(independent) variables. Results The results were compared by qualification (n = 2173) and final (n = 1197) by dividing into male (n = 1179) and female (n = 1591), and the fencing score was qualifications (male β= -.691, female β= -.533) and the finals (male β= -.632, female β= -.632), it showed the greatest influence in all. On the other hand, the swim score showed the lowest impact on both qualifications (male β=-. 021, female β=-.196) and finals (male β=-. 087, female β=-. 207). The fencing event plays a major role in passing the qualifiers and is a big variable for good performance in the finals. On the other hand, in the case of swimming scores, both men and women had the lowest impact on the final ranking, and there is a limit to the final performance of swimming scores in both qualifiers. Conclusion In conclusion, it is necessary to analyze and systemize the fencing skills of the world's best athletes, including Korean athletes, to improve the Korean fencing athletes' performance, and through such scientific analysis, a system that enables fast and flexible responses to the upcoming Olympic. Additionally, even though the importance of all sports should be levelled due to the characteristics of modern pentathlon, relative importance is biased toward fencing and swimming events are neglected. Therefore, it is deemed necessary to conduct a follow-up study on whether the scoring system in modern pentathlon consists of a scoring system that supports the records of each event and the upper and lower scoring system.